Cover Feature: Electrochemical Impedance Spectroscopy Based Biosensors: Mechanistic Principles, Analytical Examples and Challenges towards Commercialization for Assays of Protein Cancer Biomarkers (ChemElectroChem 4/2019). Issue 4 (25th January 2019) - Bertok, Tomas; Lorencova, Lenka; Chocholova, Erika; Jane, Eduard; Vikartovska, Alica; Kasak, Peter; Tkac, Jan
Abstract : The Cover Feature shows integration of electrochemical impedance spectroscopy for the analysis of clinically relevant samples toward cancer diagnostics. More information can be found in the Review by T. Bertok et al. on page 989 in Issue 4, 2019 (DOI: 10.1002/celc.201800848 ).